The Dynamics Of Value Imposition In Counseling: Ethics And Implications For The Therapeutic Relationship - Khalda Nur Aulia; Nadia Aulia Nadhirah; Nandang Budiman (Pusat Riset dan Inovasi Nasional, 2024)
The phenomenon of value imposition in counseling is a dynamic counseling process. Value imposition refers to counselors directly trying to influence clients to adopt the counselor's values, attitudes, beliefs, and behaviors. This article highlights the importance of counselors understanding the professional code of ethics applicable in the country where they practice and how value imposition is viewed from the ethics of the guidance and counseling profession in general. The research method uses a systematic literature review method, where this technique reviews articles and research systematically and explicitly, to evaluate, identify, a topic, and understand the material in depth. The conclusion of this research is that the existence of value imposition can harm the professional ethics that must be lived and is not in accordance with the existing counseling objectives.